2011
DOI: 10.3184/003685011x12982218769939
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance.: Part One: A Diagnostic Method in the Biomedical Sciences

Abstract: A review is presented of some of the ways in which electron spin resonance (ESR) spectroscopy may be useful to investigate systems of relevance to the biomedical sciences. Specifically considered are: spin-trapping in biological media; the determination of antioxidant efficiencies; lipid-peroxidation; the use of nitroxides as probes of metabolic activity in cells and as structural probes of cell-membranes; ESR coupled with materials for radiation-dosimetry; foodand drug-irradiation; studies of enzyme systems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 130 publications
0
18
0
Order By: Relevance
“…Electron paramagnetic resonance spectroscopy is based on the resonant absorption of microwave radiation by matching the energy difference of the spins of free unpaired electron in a magnetic field, and spin reversal and absorption of microwave energy can be measured [73]. The rotational effect in tissue water with a significant damping induced by the resonant absorption of microwave radiation should be considered to avoid a consequence of the high impedance at this frequency level (10 9 Hz).…”
Section: Emerging Studies Of Infrared Therapymentioning
confidence: 99%
“…Electron paramagnetic resonance spectroscopy is based on the resonant absorption of microwave radiation by matching the energy difference of the spins of free unpaired electron in a magnetic field, and spin reversal and absorption of microwave energy can be measured [73]. The rotational effect in tissue water with a significant damping induced by the resonant absorption of microwave radiation should be considered to avoid a consequence of the high impedance at this frequency level (10 9 Hz).…”
Section: Emerging Studies Of Infrared Therapymentioning
confidence: 99%
“…We assign resonance (a) to the 14 N nucleus, for which a coupling of +52.4 MHz is derived. Corresponding to 18.7 G, the coupling is significantly greater than is normally encountered for dialkyl nitroxyl radicals, which for both (3) and (4) is 15.6 G as measured in ethanol solution 30 . Resonance (b) yields either a proton coupling of +64.6 MHz using Eqn (1), or a reduced muon coupling of 65.5 MHz (A μ = 2γ μ .B res /3.1833) assuming it is from the Δm = 1 transition.…”
Section: Muonium Addition To Ethanolic Dmpo and Pbn Solutions Sorbed mentioning
confidence: 91%
“…In contrast, both radical isomers were detected in each of the other compounds. It is suggested that 43,44 , although H 2 C • -CH(Mu)SiMe 3 , H 2 C • -CH(Mu)Si(OMe) 3 and H 2 C • -CH(Mu)P(O) (OEt) 2 , are formally "primary" radicals, the stabilising effect of the second-row substituent is sufficient to increase their relative yields to detectable limits. The muon couplings are all reduced from the value in ethyl 38,39 , H 2 C • -CH 2 Mu, indeed indicating a stabilising interaction, and a minimum energy conformation (7) in which the second-row substituent (X) eclipses the unpaired-electron orbital, preferentially over the muonium atom.…”
Section: Substituent Effectsmentioning
confidence: 98%
See 2 more Smart Citations